Legionary Recruitment and Veteran Settlement During the Principate - Mann, J.C., author.
1 online resource (192 pages)
Keywords: This volume describes the pattern of recruitment of soldiers to the Roman legions and the settlement of legion veterans in Roman colonies during the period of the principate.